EKSPLORASI POTENSI ANTI MALARIA SENYAWA BIOAKTIF MORINGA OLEIFERA DENGAN PENDEKATAN IN SILICO - Novian, Dede Rival (Fakultas Farmasi UMI, 2019)
Malaria is a global human health problem and also a leading cause of death in tropical and subtropical countries. Over the past fifteen years, the prevalence of malaria has decreased by more than half. However, a new problem emerged, namely the emergence of resistance to existing malaria drugs. Therefore, efforts to develop new malaria drugs are needed to combat the malariad disease. Moringa oleifera is one of the important plants that is widely cultivated in NTT. This plant contains many important pharmacological effects such as anti-asthma, antidiabetic, anti-inflammatory, anticancer, antimicrobial, and others. However, the pharmacological effects of MO plants as antimalarials are not yet clearly known. The aim of this study is to use the in silico approach to investigate the potential of the Moringa oleifera compound which functions as a Plasmodium falciparum dihydrofolate reductase-thymidine synthase (pfDHFR-TS) receptor inhihibitor. The research method used is the in silico approach using TCMSP web based application and molecular docking simulation using USCF Chimera. The results of pharmacological tests and molecular docking simulations show that the bioactive pyhtol compound from Moringa oleifera has potential as a new malaria drug compound. Phytol compound has a MW of 296.6; the number of Hdon and Hacc is 1; OB of 33.82%; TPSA of 20.23 and the number of HL is 2.34. While the energy affinity of pyhtol compounds is -6.4 kcal / mol.